"I'm neither here, which would be bad, nor there, which would be good": the information needs of HPV+ women. A qualitative study based on in-depth interviews and counselling sessions in Jujuy, Argentina. Issue 1 (1st January 2021) - Szwarc, Lucila; Sánchez Antelo, Victoria; Paolino, Melisa; Arrossi, Silvina
Abstract: The objective of this qualitative study was to explore the information needs of HPV+ women. We conducted 38 in-depth interviews with HPV+ women in the province of Jujuy, Argentina. The interviews included a counselling session to respond to women's concerns and questions. Women perceived the information provided as good, despite having several doubts and misconceptions after receiving results of an HPV+ test. They expressed difficulties in formulating questions during the consultation due to shame, excess of information provided or lack of familiarity with technical language. They valued emotional support and being treated kindly by professionals. The perceived information needs that emerged as most important were: (1) the meaning of an HPV+ result and its relationship with cervical cancer evolution and severity; (2) continuity and timing of the care process; (3) information on the sexual transmission of the virus; (4) explanation of the presence or absence of symptoms. Women's primary unperceived information needs were: (1) detailed information about colposcopy, biopsy and treatments and their effects (including fertility consequences); and (2) deconstructing the association of sexual transmission with infidelity. Sources of information included: (1) the health care system; (2) the internet; and (3) social encounters (close friends and relatives). It is crucial to strengthen the processes for delivering results, with more thorough information, improved emotional support and active listening focused on the patient, as well as to conceive new formats to provide information in stages and/or gradually, in order to facilitate women's access to the health care system and the information they need.